EKSPLORASI PENGARUH CITRA RUMAH SAKIT TERHADAP KEPUASAN PASIEN: TINJAUAN SISTEMATIS LITERATUR - Prasetiyo, Budi; Ramadhian, M. Arief Rahman; Hurriyati, Ratih; Dirgantari, Puspo Dewi; Widjajanta, Bambang (Media Penelitian dan Pengembangan Kesehatan, 2025)
The primary challenge in measuring patient satisfaction lies in its conceptual and operational complexity. Patient satisfaction is often regarded as a subjective concept, influenced by individual expectations, experiences, and perceptions of the healthcare services received. This literature review aims to examine and summarize the impact of hospital image on patient satisfaction based on studies conducted in various countries across multiple continents. The PRISMA approach was employed in this systematic literature review, with articles collected from Google Scholar, Crossref, and PubMed databases. The articles selected were published between 2010-2024.  An in-depth analysis was conducted on 11 selected articles.  The results of the review indicate that studies on hospital image and patient satisfaction often incorporate other variables such as service quality, loyalty, and trust. Research from diverse regions, including Southeast Asia, the Middle East, Europe, and the Americas, demonstrates that hospital image significantly influences patient satisfaction. However, findings in Indonesia reveal a contrasting result, where hospital image does not affect patient satisfaction. These differences reflect unique cultural contexts, such as the importance of interpersonal relationships in Iran, ethnic diversity in Malaysia, or the high value placed on healthcare quality in Taiwan.  This review further underscores the importance of collaborative efforts among governments, hospital administrators, healthcare professionals, and marketers to enhance sustainable service quality and meet patients' evolving needs.